iTRAQ-Based Quantitative Proteomics Reveals the Energy Metabolism Alterations Induced by Chlorogenic Acid in HepG2 Cells - Shoko Takahashi (Nutrients, 2022)
Epidemiological studies have suggested that coffee consumption is associated with a decrease in the risk of developing obesity and diabetes; however, the detailed mechanisms underlying these effects of coffee consumption remain poorly understood. In this study, we examined the effects of chlorogenic acid on energy metabolism in vitro. Hepatocellular carcinoma G2 (HepG2) cells were cultured in a medium containing chlorogenic acid. Chlorogenic acid increased the activity of mitochondrial enzymes, including citrate synthase, isocitrate dehydrogenase, and malate dehydrogenase (MDH), which are involved in the tricarboxylic acid (TCA) cycle. Proteome analysis using the isobaric tags for the relative and absolute quantitation (iTRAQ) method revealed the upregulation of proteins involved in the glycolytic system, electron transport system, and ATP synthesis in mitochondria. Therefore, we propose a notable mechanism whereby chlorogenic acid enhances energy metabolism, including the TCA cycle, glycolytic system, electron transport, and ATP synthesis. This mechanism provides important insights into understanding the beneficial effects of coffee consumption.